2019
DOI: 10.2166/hydro.2019.040
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater flow simulation through the application of the FREEWAT modeling platform

Abstract: FREEWAT is a free and open source QGIS-integrated platform, developed to simulate several hydrological processes by combining the capabilities of geographic information system (GIS) for geo-processing and post-processing tools with several codes of the well-known USGS MODFLOW ‘family’. FREEWAT platform was applied for the groundwater flow simulation of a coastal aquifer system, located in northern Greece. The simulation was conducted using the MODFLOW_2005 code, the Observation Analysis Tool (a FREEWAT module … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The current study conducted by (Larbi et al, 2020), revealed a constant decline in wooded savannahs and a constant increase in agricultural land and settlement. Consequently, an earlier study conducted by (Koltsida & Kallioras, 2019), shows a constant increase in bare land and settlements at the detriment of other land use classes. Similarly, (Kumar, 2019) analyzed land use trends in the Volta Basin from 2000 to 2013.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The current study conducted by (Larbi et al, 2020), revealed a constant decline in wooded savannahs and a constant increase in agricultural land and settlement. Consequently, an earlier study conducted by (Koltsida & Kallioras, 2019), shows a constant increase in bare land and settlements at the detriment of other land use classes. Similarly, (Kumar, 2019) analyzed land use trends in the Volta Basin from 2000 to 2013.…”
Section: Discussionmentioning
confidence: 92%
“…However, large-scale hydroelectric power plants have significant The Black Volta Basin has been the subject of several studies related to hydropower potential assessment. For example, the study (Koltsida & Kallioras, 2019) used GIS and remote sensing techniques to evaluate the hydropower potential of the basin and identified several potential sites for hydropower projects. The study by (Koltsida & Kallioras, 2019) used GIS and hydrological data to assess the hydropower potential of the basin and estimated a potential of up to 700 MW.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides what was mentioned in the Introduction section, the application of the QGIS-integrated FREEWAT platform at the 13 case studies highlighted the benefits of the approach here presented. A further set of case studies may be found in Rossetto et al [17], Criollo et al [19], Cannata and Neumann [25], Perdikaki et al [87], Koltsida and Kallioras [88], and a complete list of FREEWAT-related peer-reviewed papers is available at the web address http://www.freewat.eu/peer-reviewed-papers.…”
Section: Discussionmentioning
confidence: 99%
“…Study of the effects of catchment behavior on floods, prediction of catchment response to changes in the input conditions, modeling of river behavior, real-time flood forecasting, adjusting and evaluation of water resource management and effects of river's activity such as erosion and sedimentation can be made with the help of geographic information systems (GIS). GIS can be defined as 'a computer system capable of capturing, storing, analyzing and displaying geographically referenced information; that is, data identified according to location' (Nenwiini & Kabanda 2013;USGS 2016;Koltsida & Kallioras 2019). The data for rainfall-runoff (R-R) modeling ranges from a digital elevation model (DEM) to derive physical basin characteristics, soil characteristics (for parameters about infiltration loss and soil moisture holding capability) and land use classes derived from satellite images etc.…”
Section: Introductionmentioning
confidence: 99%